2013
DOI: 10.1017/s0024282912000631
|View full text |Cite
|
Sign up to set email alerts
|

New morphological aspects of cephalodium formation in the lichenLobaria pulmonaria(Lecanorales, Ascomycota)

Abstract: Cephalodia were investigated on young and mature thalli of Lobaria pulmonaria. Cephalodia originate from contact between hyphae and cyanobacteria on the upper or lower cortex or, less frequently, in the apical zone. Young thalli were found to associate with cyanobacteria even in the anchoring zone. Cephalodia formed on the young thalli or the anchoring hyphae share the same phenotypic characteristics. In spite of being composed of paraplectenchymatous hyphae, the cortex of mature thalli preserves a considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Bacterial communities primarily colonize the (hydrophilic) lichen surfaces, yet this pattern is strikingly different from the internalized symbionts in lichens, such as the green algae (D. reticulata in L. pulmonaria), which primarily contribute to the provision of photosynthetically produced carbohydrates. The greenalgal strain is massively enriched within the fungal structures, while cyanobacterial Nostoc strains are acquired from the surfaces of L. pulmonaria recurrently during the life-time of the thallus to form internal organs devoted to nitrogen fixation in lichens (Hyvärinen et al, 2002, Cornejo andScheidegger, 2013). Conversely, the external presence of other bacteria in the lichen symbiosis recalls the helper bacteria of mycorrhizal symbioses, which provide multiple functions to mutually support and stabilize the root symbioses, including exchange of carbohydrates and vitamin provision (Frey-Klett et al, 2007;Deveau et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial communities primarily colonize the (hydrophilic) lichen surfaces, yet this pattern is strikingly different from the internalized symbionts in lichens, such as the green algae (D. reticulata in L. pulmonaria), which primarily contribute to the provision of photosynthetically produced carbohydrates. The greenalgal strain is massively enriched within the fungal structures, while cyanobacterial Nostoc strains are acquired from the surfaces of L. pulmonaria recurrently during the life-time of the thallus to form internal organs devoted to nitrogen fixation in lichens (Hyvärinen et al, 2002, Cornejo andScheidegger, 2013). Conversely, the external presence of other bacteria in the lichen symbiosis recalls the helper bacteria of mycorrhizal symbioses, which provide multiple functions to mutually support and stabilize the root symbioses, including exchange of carbohydrates and vitamin provision (Frey-Klett et al, 2007;Deveau et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The mycobiont of L. pulmonaria engulfs a green-algal photobiont (Dictyochloropsis reticulata; found in 90% of the lichen surface) and a minor cyanobacterial partner, Nostoc sp. (Cornejo and Scheidegger, 2013). Schneider et al (2011) provided an initial insight into the L. pulmonaria proteome and suggested Lobaria as an ideal model to study symbiotic processes.…”
Section: Introductionmentioning
confidence: 99%
“…For its function in nitrogen fixation of the lung lichen, Nostoc is of particular importance for the establishment of this lichen. Cornejo & Scheidegger () demonstrated that the cyanobacterial colonies are recurrently recruited from the environment and incorporated via uptake from the thallus surface into the growing thallus. Our results indicate that mosses may serve as rich reservoir of compatible Nostoc strains.…”
Section: Discussionmentioning
confidence: 99%
“…The green‐algae Dictyochloropsis reticulata is found beneath more than 90% of the lichen surface and strains of cyanobacterium Nostoc are locally restricted to gall‐like colonies, in so‐called internal cephalodia (Myllys et al ., ). These Nostoc strains are generally captured from the surface to become gradually integrated into the lichen thallus, where they primarily contribute to the symbiotic system by nitrogen fixation (Jordan, ; Cornejo and Scheidegger, ).…”
Section: Introductionmentioning
confidence: 99%